Natural Selection and the Problem of Evil: An Evolutionary Model with Application to an Ancient Debate - Fleck, Robert K. (Zygon, 2011)
Abstract. Since Darwin, scholars have contemplated what our growing understanding of natural selection, combined with the fact that great suffering occurs, allows us to infer about the possibility that a benevolent God created the universe. Building on this long line of thought, I develop a model that illustrates how undesirable characteristics of the world (stylized “evils”) can influence long-run outcomes. More specifically, the model considers an evolutionary process in which each generation faces a risk from a “natural evil” (e.g., predation, disease, or a natural disaster) subsequent to a basic resource allocation game. This allows both resource allocation and the natural evil to influence the number of surviving offspring. As the model shows, when the risk from the natural evil can be mitigated through the benevolent behavior of neighbors, the population may have increasing benevolence as a result of (1) greater risk from the natural evil and (2) a greater degree to which selfish individuals transfer resources to themselves in the resource allocation game. The main implication is that a world with evolutionary processes (in contrast to a world of static design) can allow two factors that have traditionally been considered “evils”—namely, the indiscriminate cruelty of the natural world and the capacity for humans to harm each other—to promote desirable long-run outcomes.